2019
DOI: 10.1186/s13756-019-0642-z
|View full text |Cite
|
Sign up to set email alerts
|

Risk prediction for 30-day mortality among patients with Clostridium difficile infections: a retrospective cohort study

Abstract: BackgroundCurrent guidelines have unsatisfied performance in predicting severe outcomes after Clostridium difficile infection (CDI). Our objectives were to develop a risk prediction model for 30-day mortality and to examine its performance among inpatients with CDI.MethodsThis retrospective cohort study was conducted at China Medical University Hospital, a 2111-bed tertiary medical center in central Taiwan. We included adult inpatients who had a first positive C. difficile culture or toxin assay and had diarrh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 35 publications
(72 reference statements)
1
15
0
Order By: Relevance
“…38,39 More recently, both versions of the SHEA/ IDSA criteria were validated for the prediction of 30-day mortality in a tertiary-care facility in China among a small number of CDI patients (n = 401) with AUCs between 0.60 and 0.65. 40 We similarly observed that both criteria exhibited poor discrimination (ie, AUCs near 0.60) and low positive predictive values (ie, PPVs near 0.30) in both the acute-care and subacute-care settings. Overall model metrics provide further evidence of suboptimal performance.…”
Section: Discussionsupporting
confidence: 57%
“…38,39 More recently, both versions of the SHEA/ IDSA criteria were validated for the prediction of 30-day mortality in a tertiary-care facility in China among a small number of CDI patients (n = 401) with AUCs between 0.60 and 0.65. 40 We similarly observed that both criteria exhibited poor discrimination (ie, AUCs near 0.60) and low positive predictive values (ie, PPVs near 0.30) in both the acute-care and subacute-care settings. Overall model metrics provide further evidence of suboptimal performance.…”
Section: Discussionsupporting
confidence: 57%
“…In the study conducted in Asian pacific countries, 60-day mortality in CDI patients was found to be 5.2% (Collins et al, 2020). In the study conducted in Taiwan, 30-day mortality was found to be 23.4%; and the presence of malignancy, high glucose level, 1.5-fold increase in serum creatinine were determined as independent risk factors affecting mortality (Chiang et al, 2019). Chopra et al found that, the presence of a history of malignancy or organ transplant, a history of hospitalization in the last 60 days, long-term antibiotherapy, presence of nasogastric tube or parenteral nutrition and rectal enema were found as risk factors determining the 30-day mortality (Chopra et al, 2016).…”
Section: Discussionmentioning
confidence: 95%
“…Finally, we have previously tested the device’s sensitivity and specificity in a range of laboratory and clinical conditions. 24 …”
Section: Discussionmentioning
confidence: 99%
“…Overall sensitivity and specificity of this novel electronic wearable device (to correctly identify a HH action) were 94.1% (95% CI, 91.4%-96.2%) and 99.0% (95% CI, 97.5%-99.7%), respectively. 24 …”
Section: Methodsmentioning
confidence: 99%